Strengthening Social Security Provision in Myanmar - Dutta, Puja Vasudeva (World Bank, Washington, DC, 2015)
Myanmar has a mix of contributory and non-contributory programs providing some elements of social security but for a very small section of the population. The government is considering reformsto its pension and other social security schemes. Strengthening systems and ensuring fiscal sustainability should be a priority before implementing new provisions that may strain current delivery and financial management systems and to avoid crowding out other social spending. Should the proposed reforms be introduced, a very gradual transition is advisable. The reforms should aim to develop integrated, or at least harmonized, social security schemes for both public and private sector workers in the formal sector. It will also be critical to have a clear roadmap for long-term coverage expansion to a larger share of the population, particularly the poor and vulnerable.